Correlation dimension and entropy in the assessment of sex differences based on human gait data - Świtoński, Adam; Josiński, Henryk; Polański, Andrzej; Wojciechowski, Konrad (Frontiers in Human Neuroscience, 2024)
It is experimentally demonstrated in numerous research studies that there are differences between gait performed by females and males, which appear in movements of selected body parts. Despite numerous state-of-the-art studies related to the discriminative analysis of motion capture data, the question of whether measures of signal complexity and uncertainty can extract valuable features for the problem of sex distinction remains still open. It is the subject of the paper. Correlation dimension, as well as approximate and sample entropies, are selected to describe motion data. In the numerical experiments, the collected dataset with 884 samples of 25 females and 30 males was used. The measurements took place in the Human Motion Laboratory (HML), equipped with a highly precise motion capture system. A comparative analysis between the populations of females and males using descriptive statistics, non-parametric estimation, and statistical hypotheses verification was carried out. There are statistically significant sex differences extracted by the taken measures. In general, the movements of lower limbs result in greater values of correlation dimension and entropies for females, while selected upper body parts play a similar role for males. The dissimilarities are mainly observed for hip, ankle, shoulder and head movements.